Full-thickness tumor resection of oral cancer involving the facial skin: microsurgical reconstruction of extensive defects after radical treatment of advanced squamous cell carcinoma - Moratin, Julius; Mrosek, Jan Bernd; Horn, Dominik; Semmelmayer, Karl; Ristow, Oliver; Zittel, Sven; Engel, Michael; Freier, Kolja; Hoffmann, Jürgen; Freudlsperger, Christian (Cancers, 2021)
Advanced tumors of the head and neck are challenging for the treatment specialist due to the need to synergize oncological and functional requirements. Free flap reconstruction has been established as the standard of care for defects following tumor resection. However, depending on the affected anatomic subsite, advanced tumors may impose specific difficulties regarding reconstruction, especially when full-thickness resection is required. This study aimed to evaluate reconstructive strategies and oncological outcomes in patients with full-thickness resection of the oral cavity. A total of 33 patients with extensive defects due to squamous cell carcinoma of the oral cavity were identified. Indications, reconstructive procedures, and clinical outcome were evaluated. Thirty-two patients (97%) presented locally advanced tumors (T3/T4). Complete tumor resection was achieved in 26 patients (78.8%). The anterolateral thigh flap was the most frequently used flap (47.1%), and the primary flap success rate was 84.8%. The cohort demonstrated a good local control rate and moderate overall and progression-free survival rates. Most patients regained full competence regarding oral alimentation and speech. Full-thickness tumor resections of the head and neck area may be necessary due to advanced tumors in critical anatomic areas. In many cases, radical surgical treatment leads to good oncological results. Free flap reconstruction has been shown to be a suitable option for extensive defects in aesthetically challenging regions.